2019
DOI: 10.1021/acs.jpcb.9b02655
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of HIV-1 Gag Association with Lipid Membranes

Abstract: An extensive investigation into the initial association of HIV-1 Gag with lipid membranes was conducted with second harmonic generation. The roles of the lipid phase, phospholipid 1,2-dioleoyl-sn-glycero-3-phospho-(1-myo-inositol-4,5-bisphosphate) [PI­(4,5)­P2], the presence of the myristoyl group on Gag, the C-terminus of Gag, and the presence of transfer ribonucleic acid (tRNA) in Gag–membrane association were examined using the physiologically most relevant full-length Gag protein studied thus far. The tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Therefore, hydrophobic interactions mediated by the myristoyl moiety may also be regulated by RNA binding to MA-HBR. A similar observation was also made in another in vitro study that used a purified Gag and yeast tRNA [ 76 ]. Of note, myristoylated MA under conditions that favor the myristate exposure has a weakened affinity to tRNA compared to when the myristate moiety is sequestered [ 90 ].…”
Section: The Balance Between Ma Binding To Pi(45)p2 and Rnasupporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, hydrophobic interactions mediated by the myristoyl moiety may also be regulated by RNA binding to MA-HBR. A similar observation was also made in another in vitro study that used a purified Gag and yeast tRNA [ 76 ]. Of note, myristoylated MA under conditions that favor the myristate exposure has a weakened affinity to tRNA compared to when the myristate moiety is sequestered [ 90 ].…”
Section: The Balance Between Ma Binding To Pi(45)p2 and Rnasupporting
confidence: 77%
“…Supporting the charge-based preference of Gag for PI(4,5)P2, a modeling study on MA-membrane interactions predicted that nonspecific electrostatic interactions between MA and PI(4,5)P2 were sufficient to significantly enhance membrane binding [ 34 ]. However, in vitro studies showed that HIV-1 Gag or MA binds more efficiently to PI(4,5)P2-containing lipid membranes than to charge-matched liposomes containing PS, suggesting that PI(4,5)P2 enhances Gag-membrane binding by specific interaction beyond mere electrostatic attraction [ 38 , 41 , 44 , 45 , 73 , 74 , 75 , 76 , 77 ]. Membrane flotation-based studies showed that PI(3,5)P2 and PI(3,4,5)P3 were also able to enhance the binding of Gag to liposomes, although the former is not as efficient [ 38 ].…”
Section: Determinants For Gag Binding To Pi(45)p2mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to measure and quantify APE1 binding in a label-free manner is due to resonant enhancement of the SHG signal. Specifically, the UV absorption due to the π to π* electronic transitions of the aromatic amino acids in the APE1 protein are commensurate with the second harmonic emission. Triplicate binding isotherms were obtained using the normalization procedure described previously …”
Section: Resultsmentioning
confidence: 99%
“…In vitro experiments demonstrate that Gag binds more efficiently to membranes containing PI(4,5)P 2 than those containing other acidic phospholipids such as PS [ 25 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Increasing the proportion of non-PI(4,5)P 2 acidic phospholipids to compensate for the greater negative charge of PI(4,5)P 2 does not result in a similar increase in Gag membrane binding, suggesting that Gag recognition of PI(4,5)P 2 -containing membranes is not simply charge-based but likely involves some recognition of the PI(4,5)P 2 headgroup structure [ 25 , 38 , 39 , 40 ].…”
Section: Mechanisms Regulating Hiv-1 Gag Membrane Bindingmentioning
confidence: 99%